The mechanism of action and physiological role of PLCζ at fertilisation - Hachem, A (2018)
Activation of the egg by the sperm is a key developmental event that in mammals triggered by the sperm-induced calcium oscillations. This has been proposed to be caused by the sperm-factor phospholipase C isoform zeta (PLCζ), although this remained a matter of debate for nearly 15 years. The first part of this thesis demonstrates the successful use of the novel CRISPR/Cas9 gene editing technology in targeting the coding sequence of PLCζ gene in mouse embryos that subsequently has led to the creation of the first mouse model lacking the functional expression of PLCζ. The main part of the thesis investigates the phenotype of the produced homozygous knockout male mutants. Functional analysis showed no adverse effects from the mutation on spermatogenesis, and normal sperm functional parameters. Although PLCζ-null sperm failed to trigger Ca2+ oscillations following ICSI procedures, experiments involving in vitro fertilisation, or fertilisation in vivo by natural mating, revealed that live offspring can still be conceived, albeit at greatly reduced efficiency and after a significant time delay. These findings suggest a yet-to-be identified PLCζ-independent route in mammalian egg activation that is completely dependent on sperm-egg membranes interactions. Lastly, oocytes fertilised in vivo and in vitro by PLCζ-null sperm were found to be polyspermic. The significant finding supports the role of PLCζ protein in generating the standard Ca2+ oscillations that which govern the cortical and zonal reactions and membrane establishment following fertilisation. Oolemmal membrane localisation of Juno proteins post fertilisation showed complete dependency on sperm-oocyte interaction. However, Juno shedding mechanism failed to block the polyspermic fertilisation caused by lacking the expression of PLCζ. Thus, contradicting the proposed roles of Juno in establishing oocyte membrane block to supernumerary fertilisation in mammals.